Um modelo bi-dimensional oriundo da neurociência aplicado à análise do processo de tomada de decisão: um estudo nos setores de logística e do transporte rodoviário de cargas - Akamine Junior, Arsenio (2010)
This dissertation presents an exploratory research about the decision making processes in the establishment of levels of budgetary goals by showing the results obtained from the analysis of the cognitive processes (rational and automatic) adopted by the managers of the logistics and road cargo transportation areas. The study, of quantitative nature, was accomplished with professionals that participate in the budgetary decision making process. Thirty questions were submitted to identify the behavior of the decision maker during the estimation of the budgetary goals. The data were analized by means of descriptive and multivariate statistics. The use of modelling of structural equations, suported by the PLS software, has shown that the proposed theoretical model is applied in practice and that the decision making behavior of the managers that participated in this study is different from that one found in a sample composed by managers of other sectors. The results show the importance of generating relevant concepts to the field of accounting management, in the foundations, follow-up and compliance with the corporate strategy of the Logistics and Road Cargo Transportation áreas. The data suggest that the instruments of decision support require further studies of this field, so that the automatic decision, more intuitive, does not become the predominant form of decision adopted by the managers, since while it llows for versatility and responsiveness, it is subject to many biases decisions.